READING IN THE DARK: THE TRANSCENDENCE OF POLITICAL REALITY THROUGH ART - Díaz Bild, Aída (International Journal of English Studies, 2002)
In the last three decades scholars coming from the most different fields have defended the positive, regenerating and creative qualities of the comic mode. Laughter is an agent of transcendence, a vehicle for coping with the hardships of life, a valuable talisman which allows us to survive in a world hedged with the threat of every horror and every ignominy. Reading zn the Dark, by Seamus Deane, is a very clear example of a novel in which humour helps to mitigate the harshness of the difficult and painful situations that are described, so that at the end of the book the spirit of life triumphs over death and sadness. By exploiting the narrator’s naivety Deane plays down false sentimentalism and melodrama and prevents the reader from falling into despair.